Penerapan Media Papan Jurang untuk Meningkatkan Hasil Belajar Pengurangan Bilangan pada Siswa Kelas III MI - Emi Suryani; Mubaidillah Mubaidillah; Yurnalisma Dewi (Jurnal Ragam Pengabdian, 2026)
Low mathematics learning outcomes on subtraction of hundreds to thousands remain a persistent challenge for third-grade students in Islamic elementary schools. This condition is primarily attributed to students’ limited mastery of borrowing techniques with large numbers, resulting in academic achievement below the minimum mastery criterion. This study aimed to improve students’ mathematics learning outcomes through the Ravine Board (Papan Jurang) learning medium. This study employed a Classroom Action Research design based on the Kemmis and McTaggart spiral model, conducted in two cycles comprising planning, action, observation, and reflection. Subjects were 19 third-grade students at Madrasah Ibtidaiyah Negeri 4 Bungo. Data were gathered through learning outcome tests, observation sheets, and documentation, with validity ensured through source triangulation; data were then analyzed using quantitative and qualitative descriptive approaches. Results showed progressive improvement: at pretest, the mean score was 56.32 with a 42.11% completeness rate (8/19 students); in Cycle I, the mean rose to 72.63 with 68.42% completeness (13/19 students); and in Cycle II, the mean reached 84.47 with 89.47% completeness (17/19 students), surpassing the 80% success threshold. These findings confirm that the Ravine Board medium effectively supports students’ concrete and interactive understanding of subtraction, enhancing mathematics learning quality in Islamic elementary schools.